2017
DOI: 10.3390/beverages3030039
|View full text |Cite
|
Sign up to set email alerts
|

Organic vs. Conventional Milk: Some Considerations on Fat-Soluble Vitamins and Iodine Content

Abstract: Abstract:The organic food market is considerably expanding all over the world, and the related dairy market represents its third most important sector. The reason lies in the fact that consumers tend to associate organic dairy products with positive perceptions: organic milk is eco-and animal-friendly, is not produced with antibiotics or hormones, and according to general opinion, provides additional nutrients and beneficial properties. These factors justify its higher cost. These are the reasons that explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Furthermore, Manzi and Durazzo (2017) reported higher levels of fat-soluble vitamins (β-carotene and α-tocopherol) in pasture-based organic milk than conventional milk, which could further improve the "health" quality of the milk. However, the study reported that the differences, in terms of the European Food Safety Authority (EFSA)…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Manzi and Durazzo (2017) reported higher levels of fat-soluble vitamins (β-carotene and α-tocopherol) in pasture-based organic milk than conventional milk, which could further improve the "health" quality of the milk. However, the study reported that the differences, in terms of the European Food Safety Authority (EFSA)…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
“…Manzi and Durazzo (2017) also indicated a significant reduction in iodine content of pasture-based organic milk compared to conventionally produced milk where cows are given mineral mixtures and concentrates containing supplementary iodine and selenium (Se), which is involved in iodine metabolism. Manzi and Durazzo (2017) also indicated a significant reduction in iodine content of pasture-based organic milk compared to conventionally produced milk where cows are given mineral mixtures and concentrates containing supplementary iodine and selenium (Se), which is involved in iodine metabolism.…”
Section: Enhancing Milk Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The key factor determining the profitability of dairy cow farms is their productivity. The influence of the feeding system on cows' milk yield has been demonstrated by many authors [2,27,28,[53][54][55][56][57][58][59]. In a comparison of organic and conventional systems by Bilik and Łopuszańska-Rusek [60], organic feeding of Red-and-White × Holstein-Friesian Red cows kept in natural conditions and having a lactation yield of about 7000 kg milk resulted in milk yield about 10% lower than that of cows fed conventionally (TMR) (6666.7 kg vs. 7353.4 kg).…”
Section: Milk Yieldmentioning
confidence: 98%
“…Research by many authors [2,[26][27][28][50][51][52][53][54] indicates that the specific environmental conditions (mainly feed type and quality) on a farm focused on milk production affect the quality of raw milk, and consequently, dairy products.…”
Section: Milk Production System and The Quantity And Quality Of Raw Milk And Manufactured Dairy Productsmentioning
confidence: 99%